2019
DOI: 10.1155/2019/4621372
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Vitamin D and Liver Function and Liver Fibrosis in Patients with Biliary Atresia

Abstract: Objectives To detail the effects of vitamin D (VD) deficiency and assess the relationships between VD deficiency and liver function and liver fibrosis in patients with biliary atresia (BA). Methods In this study, BA patients confirmed by intraoperative cholangiography were enrolled between January 2017 and February 2019. Preoperative serum 25-(OH)D level, liver function, serum biomarker levels of liver fibrosis, and histopathologic features were recorded. Deficiency, insufficiency, and sufficiency of VD were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Previous animal studies have confirmed that the binding of active vitamin D and VDR can regulate activity of the TGF-β signaling pathway in HSCs, thereby inhibiting expression of fibrosis genes and expression 28 , 31 and deposition of types I and III collagen 30 , 41 . A recent study found that serum N-terminal peptide of procollagen III, an indicator of liver fibrosis, was negatively correlated with 25(OH)D in children with BA 35 . At present, there has been no study on the mechanism of 25(OH)D deficiency in BA, nor on the mechanism of the relationship with liver fibrosis.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous animal studies have confirmed that the binding of active vitamin D and VDR can regulate activity of the TGF-β signaling pathway in HSCs, thereby inhibiting expression of fibrosis genes and expression 28 , 31 and deposition of types I and III collagen 30 , 41 . A recent study found that serum N-terminal peptide of procollagen III, an indicator of liver fibrosis, was negatively correlated with 25(OH)D in children with BA 35 . At present, there has been no study on the mechanism of 25(OH)D deficiency in BA, nor on the mechanism of the relationship with liver fibrosis.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, as more studies have gradually revealed the internal relationship between vitamin D deficiency and liver fibrosis, researchers have begun to pay attention to this problem. Ng et al 34 detected the pre-HPE 25(OH)D level in 92 children with BA, and found that 98.9% of the children had 25(OH)D deficiency or insufficiency, and only one (1.1%) had a normal level of 25(OH)D. Zhuang et al 35 examined the 25(OH)D level before HPE of 161 BA cases, and found that 96.3% of the children had 25(OH)D deficiency or insufficiency. However, these studies confirmed deficiency of 25(OH)D in children with BA, but did not further investigate the cause of that deficiency and its effect on liver lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in an inhibitory signal on the TGF-beta/SMAD-dependent transcriptional response of pro-brotic gene in the hepatic stellate cells has been postulated as a pathogenesis link. [10][11][12] An animal model study also showed that vdr −/− mice developed more bile duct injury by losing bile duct epithelial polarity after bile duct ligation compared to the wild-type strains. [13] Moreover, a clinical observational study demonstrated a negative correlation between vitamin D levels and NAFLD brotic score.…”
Section: Discussionmentioning
confidence: 99%